Factors influencing spousal support for women with perinatal depression in seeking formal assistance: a qualitative study - Zou, Qinhan; Yang, Yingzi; Liu, Xianliang; Wang, Tingting; Chen, Ruizhe; Duan, Xia (Frontiers in Public Health, 2024)
ObjectiveSeeking formal help can significantly improve the outcomes of perinatal depression (PND). However, currently, women with PND are not consistently seeking formal help. Research indicated that spouses played a crucial role in helping women recognize PND and encouraging them to seek formal help. This study aimed to explore the factors that prevent spouses from supporting women with PND in seeking formal help, based on the Knowledge-Attitude-Practice (KAP) theory.MethodsThis is a qualitative study, utilizing semi-structured interviews to explore the factors that influence spouses to support women with PND to seek formal help. The interviews were conducted at a tertiary hospital in Shanghai, China from September 2023 to October 2023. Purposive sampling was used, and the sample size was determined by data saturation. Data analysis was conducted using Colaizzi’s seven-step method.ResultsTwelve spouses had a mean age of 34.92 years (SD 5.81); n = 7 (58.33%) were new fathers. The influencing factors identified in this study can be explained by KAP theory, ultimately three major themes and six sub-themes emerged: (1) individual knowledge factors: lack of proper recognition of PND, (2) individual attitude factors: negative attitude toward PND screening and treatment and (3) service provider factors: imbalance between supply and demand for perinatal mental health services.ConclusionSpouses who lacked supportive behavior were influenced by individual factors, including knowledge factors and attitude factors, as well as service provider factors. These identified factors can guide future research and the development of interventions to improve perinatal mental health services and encourage family support in seeking formal help.